2017
DOI: 10.3389/fmicb.2017.01252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physiochemical Factors on Prokaryotic Biodiversity in Malaysian Circumneutral Hot Springs

Abstract: Malaysia has a great number of hot springs, especially along the flank of the Banjaran Titiwangsa mountain range. Biological studies of the Malaysian hot springs are rare because of the lack of comprehensive information on their microbial communities. In this study, we report a cultivation-independent census to describe microbial communities in six hot springs. The Ulu Slim (US), Sungai Klah (SK), Dusun Tua (DT), Sungai Serai (SS), Semenyih (SE), and Ayer Hangat (AH) hot springs exhibit circumneutral pH with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 72 publications
9
59
0
Order By: Relevance
“…Medrano-Santillana et al found that the bacterial communities in volcanic soils were characterized by the prevalence of Firmicutes, Proteobacteria, and Actinobacteria [65,66]. The same phyla were disclosed in this study, along with others, such as Planctomycetes and Bacteroidetes, in agreement with other studies showing that members of these phyla have been found in a wide variety of environments, confirming their strong versatility.…”
Section: Bacterial Communities Studysupporting
confidence: 91%
“…Medrano-Santillana et al found that the bacterial communities in volcanic soils were characterized by the prevalence of Firmicutes, Proteobacteria, and Actinobacteria [65,66]. The same phyla were disclosed in this study, along with others, such as Planctomycetes and Bacteroidetes, in agreement with other studies showing that members of these phyla have been found in a wide variety of environments, confirming their strong versatility.…”
Section: Bacterial Communities Studysupporting
confidence: 91%
“…DG devised the topic, supervised paper structure and data collection, conducted literature search, created figures and wrote the paper. et al, 1977;Kavak and Karadogan, 2012;Pontefract et al, 2017;Tambekar et al, 2010 Terrestrial hot springs/geothermal waters 15 -270 0.02 -9.8 0.1 -7.2 b 0.0002saturation Chan et al, 2017;Delmelle and Bernard, 1994;Namsaraev et al, 2003;Qi et al, 2017;Taran, 2009 Polar environments -98.6 -24.3 4.6 -9.6 0.1 -35.5 c 0 -40.2 Aislabie et al, 2006;Dickson et al, 2013;Samarkin et al, 2010;Scambos et al, 2018;Siegert et al, 2001 Deep-sea floor and trenches -1.9 -13.8 d 7.3 -8.1 2.1 -112 3.4 -3.9 Danovaro et al, 2010;Emeis et al, 1996;Mantyla and Reid, 1983 Deep-sea hydrothermal vents < 1 e -464 4 -11 2.1 -50.7 0.1 -8 Konn et al, 2009;Koschinsky et al, 2008;McDermott et al, 2018 Deep hypersaline anoxic basins 10 -65 5.4 -8.6 2.1 -40.5 4 -50 f Karbe, 1986;Mapelli et al, 2017;Merlino et al, 2018;Yakimov et al, 2013Yakimov et al, , 2015 Subsurface ecosystems 3.25 -< 400 g~1 -12.8 < 800 h 0.05 -saturation i Becker et al, 1984;Frank et al, 2016;Lechmann et al, 2014;Prieto et al, 2017;Roadcap et al, 2006;Waldron et al, 2007 Deserts j -19.4 -70 6.8 -10 nr 0.02 -30.8 Dion et al, 2008;…”
Section: Future Directions and Outlookmentioning
confidence: 99%
“…Worthy of note is that the phylum Fusobacteria, a group of gram-negative non spore formers, were found but not exclusively in the Ikogosi Warm Spring. This bacterial phylum was also reported as part of the prokaryotic biodiversity of a Malaysian circumneutral hot springs [41].…”
Section: Discussionmentioning
confidence: 73%